ANALISIS PENGARUH PROGRAM PELATIHAN DAN EDUKASI ONBOARDING KANTOR PERWAKILAN BANK INDONESIA KEDIRI TERHADAP PENDAPATAN USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) DI WILAYAH KEDIRI - Rahmawan, Andri; Anggraeni, Puspitasari Wahyu (Contemporary Studies in Economic, Finance and Banking, 2022)
Bank Indonesia as the Central Bank plays a role in the development of the Micro, Small and Medium Enterprises (MSME) sector, which is one form of Bank Indonesia's support for Micro, Small and Medium Enterprises (MSMEs) by providing technical assistance to MSMEs through training and education programs. Micro, Small and Medium Enterprises (MSMEs). This study aims to determine the influence of onboarding training and education programs at the Bank Indonesia Kediri Representative Office on the revenue of Micro, Small and Medium Enterprises (MSMEs) in the Kediri region. This research is a quantitative research, with the research subjects are 40 Micro, Small and Medium Enterprises (MSMEs) in the Kediri region who take part in the onboarding training and education program at the Kediri Bank Indonesia Representative Office. The data collection technique of this research used a questionnaire. The data analysis of this research used multiple linear regression analysis. The results of this study indicate that the onboarding training and education program for the Bank Indonesia Representative Office Kediri has a positive and significant influence on the revenue of Micro, Small and Medium Enterprises (MSMEs) in the Kediri region.